Cryptococcus neoformans isolation from swallow (Hirundo rustica) excreta in Iran - Mohammad T. Hedayati; Sabah Mayahi; Mahdi Fakhar; Tahereh Shokohi; Mohammad Majidi (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
Cryptococcus neoformans is an encapsulated yeast that can cause cryptococcosis, a life-threatening infection that mainly occurs in immunocompromised patients. The major environmental sources of C. neoformans have been shown to be soil contaminated with avian droppings. In the present study, we evaluated the isolation of C. neoformans from swallow (Hirundo rustica) excreta in two northern cities of Iran. Ninety-seven swallow droppings were evaluated and 498 yeast-like colonies were isolated and identified as Rhodotorula spp. (62.8%), Candida spp. (28.5%)and C. neoformans (8.7%). Cryptococcus neoformans was isolated from 5/97 (5.2%) of collected samples. Min-Max colony forming units (CFU) per one gram for the positive samples were 3-10 C. neoformans colonies. The total mean CFU per one gram for the positive samples was 4.8. The results of this study demonstrate that excreta of swallow may harbor different species of potentially pathogenic yeasts, mainly C. neoformans, and may be capable of disseminating these fungi in the environment.